Label free nano-aptasensor for interleukin-6 in protein-dilute bio fluids such as sweat. Issue 17 (20th April 2016) - Kumar, L. S. Selva; Wang, Xiao; Hagen, Joshua; Naik, Rajesh; Papautsky, Ian; Heikenfeld, Jason
Abstract : A sub-pM limit of detection label-free sensor is presented for interleukin-6 based on impedimetric measurement of a gold nanoparticle/aptamer-modified electrode in artificial sweat. Abstract : A sub-pM limit of detection label-free sensor is presented for interleukin-6 based on impedimetric measurement of a gold nanoparticle/aptamer-modified electrode in artificial sweat.